Retinal vessel wall signs and the 5 year incidence of age related maculopathy: the Blue Mountains Eye Study. Issue 1 (23rd December 2003) - Wang, J J; Mitchell, P; Rochtchina, E; Tan, A G; Wong, T Y; Klein, R
Abstract : Aims: To assess whether retinal arteriolar wall changes (focal narrowing and arteriovenous nicking) are associated with an increased 5 year risk of age related maculopathy (ARM). Methods: The Blue Mountains Eye Study examined 3654 residents aged 49+ years living in a defined area, during 1992–4 (82.4% participation). After 5 years, 2335 surviving participants (75.1%) were re-examined during 1997–9. Retinal photographs were graded using the Wisconsin ARM grading system. Incident late (neovascular or atrophic) or early stage ARM was defined using a side by side grading method. Focal arteriolar narrowing (localised constricted arteriolar segments causing a sausage-like appearance), and arteriovenous (AV) nicking (constriction on both sides of the venule where crossed by an arteriole), were graded by comparison with standard photographs. All retinal vessels passing through a circumferential zone 0.5–1.0 disc diameters from the optic disc margin were measured from digitised images. Summarised estimates for central retinal arteriolar equivalent (CRAE) represent an average diameter of arterioles for that eye. Associations were assessed after adjusting for age, sex, smoking, mean arterial blood pressure, and other vascular risk factors. Results: Of 2314 baseline participants at risk of late stage ARM, either late stage lesion developed in 34 participants (1.5%). Of 2203 at risk of early stage ARM, this sign developed in 197 participants (8.9%). Focal arteriolar narrowing was present at baseline in at least one eye of 162 survivors (6.9%) and severe AV nicking was present in 187 people (8.1%). Over 5 years, 4.9% of subjects with and 1.2% of those without focal narrowing developed either late stage ARM lesion, age adjusted relative risk (RR) 2.3, 95% confidence interval (CI) 1.0 to 5.1, multivariate adjusted odds ratios (OR) 2.1 (95% CI 0.9 to 4.9). Similarly, 3.7% of subjects with and 1.3% of those without severe AV nicking developed late ARM lesions, age adjusted RR 2.1 (95% CI 0.9 to 5.1), multivariate adjusted OR 2.2 (95% CI 0.9 to 5.6). Corresponding age adjusted RR and multivariate adjusted OR for development of early stage ARM were 1.4 (95% CI 0.9 to 2.0) and 1.3 (95% CI 0.8 to 2.1) for focal arteriolar narrowing, and 1.6 (95% CI 1.0 to 2.3) and 1.8 (95% CI 1.1 to 2.9) for severe AV nicking, respectively. No associations between baseline CRAE and 5 year incident late or early stage ARM were found. Conclusions: Although of borderline statistical significance, the consistent associations found in this study suggest that structural retinal arteriolar changes may either contribute to ARM progression or may share common pathological pathways with ARM.